On the V(I)Erge: Jean-Luc Nancy, Christianity, and Incompletion - Fritz, Peter Joseph (Heythrop journal, 2014)
This article explores how Jean-Luc Nancy attempts to gain critical traction on Christianity by proscribing thinking of completion. First, it describes Nancy's deconstruction of Christianity as stemming from his aesthetic redirection of Heidegger's thinking of finitude. Second, it further details Nancy's noetic declension of Heidegger via Kant and Lyotard, where the imagination and aesthetic communication are deemed impossible. Third, it examines Nancy's treatment of paintings of the Virgin Mary who, for Nancy, exemplifies his brand of incompletion. Nancy's work on Mary reveals both the oversights and the insights of his deconstruction of Christianity, which Catholic theology should seriously engage.